KONSEP HARI TUHAN DALAM PERSPEKTIF TEOLOGI SOSIAL MENURUT AMOS 5:18-20 - Laia, Imran; Panjaitan, Firman (LOGIA: Jurnal Teologi Pentakosta, 2025)
This study aims to explain the meaning of the day of the Lord as proclaimed in Amos 5:18-20. In some views it is said that the day of the Lord is the day of preaching about God's salvation to mankind, especially his chosen people. But Amos spoke differently, he actually showed that the day of the Lord is the day of God's judgment for the social sins committed by the Israelites. This research uses descriptive qualitative method with text criticism interpretation approach. The result of this study is the affirmation of God's judgment day that occurs when God's day comes. God will act decisively by punishing every sin of the people of Israel, especially social sins. Because Israel could not force any of their religious practices and worship into social life, the Israelites fell into social sins. It was in this situation that the day of the Lord came and judged the Israelites so that they would repent of their social sins.